Aplikasi dengan Metode UCD (User-Centered Design) pada BLK Don Bosco Sumba - Paulina Indriani Mori Uma; Gergorius Kopong Pati; Alexander Adis (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The rapid development of information technology requires training institutions to adapt in order to provide services that are effective, efficient, and aligned with user needs. Don Bosco Sumba Vocational Training Center (BLK) as an institution focused on enhancing community skills faces challenges in providing a system that is easily accessible and usable by trainees, instructors, and administrators. This study aims to design and develop a web- and mobile-based application using the User-Centered Design (UCD) approach to produce a system that truly fits user needs and preferences. The UCD method was applied through several stages, including user and context identification, needs analysis, solution design, and iterative evaluation of the developed prototype. Data were collected through interviews, observations, and questionnaires administered to various users within Don Bosco Sumba BLK. The findings show that the implementation of the UCD method improved usability, streamlined administrative processes, and enhanced user satisfaction with the developed system. Therefore, the development of this UCD-based application not only supports the improvement of service quality but also strengthens the effectiveness of training management at Don Bosco Sumba BLK. The implications of this study highlight the importance of applying a user-centered approach in the development of information systems within the vocational training sector.